LITERARY ECOLOGY AND LOCAL GENIUS OF BUGIS-MAKASSAR IN THE NOVEL YANG TERSISA DARI YANG TERSISA, WRITTEN BY NURHADY SIRIMOROK - Lewa, Inriati; Amir, Syahwan Alfianto (Prosiding Konferensi Internasional Kesusasteraan, 2025)
This article aims to describe the relationship between humans and nature and humans towards local genius in the novel Yang Tersisa dari Yang Tersisa by Nurhady Sirimorok. This study is analyzed through an ecocriticism approach based on Greg Garrard's theory, focusing on his perspective regarding the concept of Dwelling. Based on Georgic's point, humans' interaction with nature describes interactions that destroy nature. The results of this analysis show that implicitly, in the novel, there is a phenomenon of exploitation of the forest that makes wild boars leave their habitat in search of food to survive. Furthermore, this article not only improves the understanding of literary ecology but also shows the values of the local genius of the Bugis-Makassar tribe in Indonesia from the aspect of advice and supernatural elements, offering valuable lessons for navigating a world increasingly shaped by technological advancements.